Interpersonal Communication and Student Geography Learning Outcomes Through the Talking Stick Type Cooperative Learning Model - Wijayanti, Detti; Khairani, Khairani; Anwar, Syafri; Afdhal, Afdhal (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
One of the problems faced by the world of education is the problem of weakness of the learning process, especially during the COVID-19 pandemic which disrupts the student learning process. Learning activities are a supporting factor for the success or failure of the learning activities carried out. Learning activities can connect the lessons that have been learned with the knowledge they already have. This study aims to describe efforts to improve interpersonal communication and student geography learning outcomes through the talking stick type of cooperative learning model. The method used is a Systematic Literature Review (SLR). The data sources analyzed by the literature can be in the form of books, scientific articles, research journals, research reports, seminar proceedings, and so on. The results obtained concluded that the better the students' interpersonal relationships, the more open people were to express themselves. Through the Talking Stick Type Cooperative learning model, after students receive their learning experience and the results can be used by the teacher to be used as a measure or criterion for achieving an educational goal.